Combination antifungal therapy with voriconazole for persistent candidemia in very low birth weight neonates - Turan, Ozden; Ergenekon, Ebru; Hirfanoğlu, I Murat; Onal, E Esra; Baş, V Nijat; Türkyilmaz, Canan; Koç, Esin; Atalay, Yildiz (The Turkish Journal of Pediatrics, 2011)
The purpose of this article is to report our experience with intravenous voriconazole therapy in the treatment of persistent Candida septicemia in very low birth weight (VLBW) neonates. Candidiasis was defined if an infant had a positive blood culture. Ten VLBW newborns developed Candida sepsis, and candidemia persisted in 6 of them despite 3 to 21 days of antifungal therapy with amphotericin B, either conventional or liposomal, and fluconazole. After the addition of voriconazole, clearance of Candida was achieved within 3-7 days of treatment. Antifungal therapy combination with liposomal amphotericin B and voriconazole was continued for at least two weeks after two negative cultures 48 hours apart. We conclude that considering the hazardous effects of Candida infections in preterm newborns, voriconazole can be added to the treatment of fungal sepsis in newborns who still have persistent candidemia despite conventional antifungal management. More clinical information is needed before voriconazole can be used as a first-line drug in antifungal therapy in newborns.